Guide :

find the difference quotient of -x^2+9x

Find the difference quotient

Research, Knowledge and Information :

Mathway | Find the Difference Quotient f(x)=x^2+9x-7

Precalculus. Find the Difference Quotient f(x)=x^2+9x-7. ... [x 2 1 2 π ∫ ...

Difference Quotient - analyzemath.com

Difference Quotient. What is the difference quotient in calculus? We start with the definition and then we calculate the difference quotient for different functions.

THE DIFFERENCE QUOTIENT

from the difference quotient that the elementary formulas for derivatives are developed. II.

The Difference Quotient 3 | Coolmath.com

find the difference quotient: Do the blob thang: * If you do ...

• Find The Difference Quotient Of X 2 9x - Video Results

• Difference Quotient for x^2
• Find the difference quotient for f(x)=3x^2-2x
• How to find the difference quotient of f(x) = x/(x+8) (HW2: Problem 2)
• Find the difference quotient of f(x)=2x^2-3x+5
• Mathway | Find the Difference Quotient f(x)=9x-x^3

www.mathway.com/popular-problems/Precalculus/421832

Precalculus. Find the Difference Quotient f(x)=9x-x^3. Consider the difference quotient formula.

• find the difference quotient of x 2 9x - Yahoo Answers Results

• difference quotient ?

The difference quotient is [f(x+h) - f(x)]/h (your book may use some other notation, such as Δx, for the change in x) f(x+h) = -7(x+h)² + 9(x+h) - 6 Expanding this, f(x+h) = -7(x² + 2xh + h²) + 9(x+h) - 6 = -7x² - 14xh - 7h² + 9x + 9h - 6...

• For the function f( x )=-7x^ 2 + 9x -6, find the difference quotient and...

Recall that the difference quotient is: [f(x + h) - f(x)] / h So we have that the difference quotient is: f(x + h) = -7(x + h)^2 + 9(x + h) - 6 f(x) = -7x^2 + 9x - 6 [f(x + h) - f(x)] / h = [-7(x + h)^2 + 9(x + h) - 6 - (-7x^2 + 9x - 6)] /...

• Finding the Difference Quotient !? (math)?

By definition, the difference quotient is [f(x+h) - f(x)] / h For the given f(x), this is { [3(x+h)³ + 5(x+h) + 2] - (3x³ + 5x + 2) } / h If you expand the terms in the square brackets and then subtract the terms in parentheses, you should...

• Suggested Questions And Answer :

f(x)=x^3 solve using the difference quotient

To find the difference quotient at any point (x,f(x)), we need to find f(x) for a value of x just a tiny bit bigger than x. This value of x has a value of x+h, where h is a very tiny quantity. f(x+h)=(x+h)^3. This can be expanded as x^3+3x^2h+3xh^2+h^3. The difference between this and f(x)=x^3 is therefore 3x^2h+3xh^2+h^3. The difference in the x value is, of course, h by definition of h. So the difference quotient is (3x^2h+3xh^2+h^3)/h, being the vertical displacement divided by the horizontal displacement. This comes to 3x^2+3xh+h^2. Because h is very tiny, infinitesimally small, in fact, we can ignore the terms involving h, leaving us with 3x^2, the difference quotient. The difference quotient can be used to calculate approximations in evaluating the cubes of numbers close to known cubes. If we want the cube of 3.05, we know that 27 is the cube of 3, so we add 3*9*0.05=1.35 to 27 to get an approximation, i.e., 28.35. The actual value is closer to 28.373.

How do I find the simplified form of the difference quotient for the function: f(x) = ax^4

How do I find the simplified form of the difference quotient for the function: f(x) = ax^4  this is simple, remember that the a is a constant.  so there is NO PRODUCT. f'(x) = 4ax^3

Evaluate the difference quotient for the function f(x)=x^2+5

To find the difference quotient consider f(x+h), where h is a very tiny value. If we evaluate this we get f(x+h)=(x+h)^2+5, which expands to x^2+2xh+h^2+5. If we subtract f(x)=x^2+5 from this we get 2xh+h^2. The difference quotient is this divided by h, giving us 2x+h. We ignore h because it's very tiny, infinitesimal. So the difference quotient is 2x. Note that the constant 5 disappears and the power of x is reduced.

Three divided by the sum of x and 3 equals the quotient of 9 and the difference of x and 3.

??????????????? "quoeshent" ??????????????... look tu me like yu hav 2 FRAKSHUNS... 3/(x+3) =9/(x-3)... 3=9*(x+3) /(x-3)... 3*(x-3) =9*(x+3)... 3x-9 =9x+27... (9x-3x) +(27+9)=0... 6x=36... x=36/6=6

find the difference quotient of -x^2+9x

???????????????????? "quoeshent" ?????????????????? ??? yu want FRAKSHUN ??? 9x-x^2 look like x*(9-x)

find the difference quotient and simplify answer -4y2+6y(1+0)-4y2+6y(1)/0

estimate. then find the difference 607-568

a wire of length l is cut into two parts. One part is bent into a circle and the other into square

If the radius of the circle is d then its area is (pi)d^2 and its circumference is 2(pi)d, the length of wire we need to make the circle. The length of the remainder of the wire is l-2(pi)d, out of which we make the square. So the side of the square is a quarter of this perimeter, 1/4(l-2(pi)d), and the area of the square is the square of this side, 1/16(l-2(pi)d)^2. The sum of the areas of the circle and square is (pi)d^2+1/16(l-2(pi)d)^2. We need the minimum value of this expression, where the variable is d. So we differentiate it with respect to d. That's the same as getting the difference quotient. The expansion of 1/16(l-2(pi)d)^2 is l^2/16-1/4(pi)ld+1/4(pi)^2d^2. [Please distinguish between 1 and l in the following.] The difference quotient is zero at a maximum or minimum, so we have 2(pi)d-l/4(pi)+1/2(pi)^2d=0. We can take out (pi), leaving 2d-l/4+1/2(pi)d=0. Multiply through by 4 to get rid of the fractions: 8d-l+2(pi)d=0, from which d=l/(8+2(pi)). Half the length of the side of the square is 1/8(l-2(pi)d). If we substitute for d in this expression we get 1/8(l-2(pi)l/(8+2(pi)))  = l/8((8+2(pi)-2(pi))/(8+2(pi)) = l/8(8/(8+2(pi)) = l/(8+2(pi)) = d (QED). Therefore the radius of the circle = half the length of the side of the square is either a maximum or minimum value of the expression for the sum of the areas of the circle and square. We can see that this expression gets bigger as d gets bigger, because (pi)d^2 has a positive value always, so we do indeed have a minimum rather than a maximum. We can substitute d=l/(2(4+(pi))) in the expression for the sum of the areas and we get the minimum: (pi)d^2+1/16(l-2(pi)d)^2 = (pi)l^2/4(4+(pi))^2 + 1/16(l-2(pi)l/(2(4+(pi)))^2 = (pi)l^2/4(4+(pi))^2 + l^2/16(1-(pi)/(4+(pi))^2 = (pi)l^2/4(4+(pi))^2 + l^2/16(4+(pi)-(pi))^2(4+(pi))^2 = (pi)l^2/4(4+(pi))^2 + l^2/(4+(pi))^2 = l^2/(4(4+(pi))) or (l^2/4)*1/(4+(pi)) Sorry, it was getting difficult to represent the expressions using this tablet so I've had to accelerate the last bit! I hope I didn't make any mistakes!

if 43/240<x1/x2<17/94, x3 is minimum possible value of x2 find 53*x3

Question: if 43/240 Read More: ...